Rekonstruksi Frasa Fasilitas Lainnya Dalam Tindak Pidana Korupsi Terkait Gratifikasi Seksual - Ade Irma Suryani; Ahmad Hasan Basri (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
The Corruption Law requires adjustments to create legal certainty, therefore in this study the researcher will examine the reconstruction of the Elucidation of Article 12B Paragraph (1) in the Corruption Law. The reconstruction of this article is intended to create legal certainty regarding sexual gratification so that perpetrators of sexual gratification crimes can be punished. The research method used in this research is normative legal research. The approaches used in this study are statutory approaches, historical approaches, and conceptual approaches. The results of the study state that when the corruption crime regulations have not stated and regulated explicitly regarding sexual gratification, especially in the explanation of the phrase